1984
DOI: 10.1007/bf02405371
|View full text |Cite
|
Sign up to set email alerts
|

Oophorectomy and cortical bone remodeling in the beagle

Abstract: Cortical bone remodeling measurements were carried out on the ribs of 6 spayed and five control Beagle dams which had been subjected to a period of observation equal to more than one sigma of cortical bone remodeling activity. The results of the measurements of static and dynamic parameters indicate that the lack of ovarian hormones does not produce a major alteration in the rates of cortical bone remodeling, but does result in an increase in the number of resorption spaces per mm2 of cortical bone without alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

1989
1989
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 8 publications
1
15
0
Order By: Relevance
“…Ovariohysterectomy does not have a major effect on cortical bone remodeling parameters in the beagle, although there may be a slight increase in the resorption phase (20). However the principal benefit of ovariohysterectomy is the abolition of the estrous cycle.…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…Ovariohysterectomy does not have a major effect on cortical bone remodeling parameters in the beagle, although there may be a slight increase in the resorption phase (20). However the principal benefit of ovariohysterectomy is the abolition of the estrous cycle.…”
Section: Methodsmentioning
confidence: 97%
“…However the principal benefit of ovariohysterectomy is the abolition of the estrous cycle. The female beagle has a 6 month estrous cycle and the natural estrogen levels fluctuate over this period (20). To our knowledge, there have been no studies of changes in remodeling parameters in relation to this fluctuation.…”
Section: Methodsmentioning
confidence: 99%
“…Although it can vary widely among dogs, heat cycles include a long anestrus interval of up to 150 days, during which circulating estradiol concentrations remain comparatively low because of ovarian quiescence. During most canine bone loss experiments in which peripheral estradiol concentrations were measured after ovary removal, significant reductions in estradiol have been reported based on comparisons to sham dogs, (24)(25)(26) although in one experiment a significant drop in estradiol concentrations took up to 10 wk to become apparent. (27) Ovariohysterectomy (OHX) or spaying entails physical removal of the ovaries, oviducts, uterine horns, and the uterus.…”
Section: Reinwald and Burrmentioning
confidence: 99%
“…(55) The fallibility of the castrated dog model for bone loss research may have evolved more as a result of inconsistent study designs rather than an inherent unreliability of the dog itself. A systematic comparison of available OVX and OHX dog studies (24)(25)(26)(27)(42)(43)(44)(45)(46)(47)(48)(59)(60)(61)(62)(63) showed that the age range of animals has often been wide, the numbers of dogs in experimental groups are sometimes small, use of histomorphometric endpoints (e.g., BV/TV) for small group sizes requires very large differences given the high SD (∼25%) for this method of assessment, (57) the site examined may not be representative of bone loss at other sites, dietary calcium is often overabundant or indeterminable, complete extrication of ovarian tissue is not routinely confirmed at necroscopy, and the timing of ovariectomy may not have been well planned in relation to estrous cycle stage. Castration during times of peak progesterone concentrations can potentially result in heterogeneous hormonal profiles among dogs in shorter-term experiments.…”
Section: Dogsmentioning
confidence: 99%
“…When the role of local factors is considered as influential to bone formation rate to any significant degree, then it is appropriate to employ tissue from a model taken from sites where there are loading dynamics not dissimilar to the human. In this regard, the NHP is superior to other models such as the rat [Danielsen et al, 1992;Jee et al, 1990;Kalu, 1991] and the dog [Faugere et al, 1990;Snow et al, 1984], which have significant shortcomings in terms of biomechanics, growth properties, endocrinology, and cortical bone tissue morphology. The femoral neck of the NHP has the basic triangular shape of the human, with variation in cortical thickness [Hotchkiss, 1999], as opposed to the round shape with uniform cortical thickness seen in rats [Bagi et al, 1997].…”
Section: The Nonhuman Primate (Nhp) Model Of Osteoporosismentioning
confidence: 99%